Text analysis: linguistics, Semantics, Pragmatics in the Cognitive Approach - Kharlamov, A.A.; Yermolenko, T.V. (Управляющие системы и машины, 2015)
The cognitive approach to linguistic information analyzed by the human is considered. The processes of information processing are studied at various linguistic levels: morphological, lexical, syntactic and semantic levels for separate sentences, and finally, semantic and pragmatic levels for the text as a whole. As an example of the following processing, representation of the pragmatic level is identified as a chain of extended predicate structures of a particular text processing, pragmatic processing, chain of extended predicate structures. Розглянуто когнітивний підхід до аналізу лінгвістичної інформації та процеси обробки інформації різних лінгвістичних рівнів: морфологічного, лексичного та ін. Як приклад подано ланцюжок розширених предикатних структур конкретного тексту. Рассмотрены когнитивный подход к анализу лингвистической информации и процессы обработки информации разных лингвистических уровней: морфологического, синтаксического и др. В качестве примера приведена цепочка расширенных предикатных структур конкретного текста.